Standing at the Crossroads: Taking the Path of Least Resistance or Forging Ahead Toward Action-Oriented Assessment? - Jaci Webb-Dempsey (Educational Considerations, 2003)
Over the past decade, many universities and colleges who prepare teachers have begun the hard work of establishing partnerships with K–12 schools in order to simultaneously renew the preparation and practice of teachers.